Accessible built environment for the elderly and disabled in Malaysia: hotel as case studies - Abdul Rahim, Asiah; Abd. Samad, Nur Amirah (Penerbit Universiti Sains Malaysia, 2010)
In Malaysia, it has become of increasing importance to study ways to improve the level of accessibility in buildings for the elderly and disabled people in the built environment, especially in hotels and resorts. The methods used in this study to identify areas to improve are access audits, table research and interviews. The data from these studies are analysed using a descriptive analysis based on access audits, observations, plan analysis, photographs and questionnaires. Access audits were carried out in two hotels and resorts in July and November 2007 in selected areas of East Malaysia. The selected hotels and resorts were constructed in the 1980s; one is located at the countryside and the other in the city centre. The findings will allow the building provider to upgrade existing facilities in order to accommodate accessible built environment for the elderly and disabled people. This will allow the elderly and disabled people to move freely, safely and being more easily integrated with the society in areas of public building and public spaces.